Utilização da espectroscopia Raman para monitorar a cura de tintas epóxi aplicadas em tanques de armazenamento de petróleo - Medeiros, Viviana Maria Mello de (2010)
Epoxy paints are organic coatings applied on the metal surface and hindering the contact surface with the corrosive medium. The condition of curing a resin is of fundamental importance because it affects the mechanical behavior of crosslinked resin. This paper aims to present a study monitoring the curing process of two types of epoxy paints, primer and finishing with the variation of temperature and time, Since the polyamide as curing agent in paint primer and polyamine in paint topcoats. The technique of Raman spectroscopy was used to monitor the cure of epoxy resin and the technique of thermogravimetric analysis (TGA) was used only to verify the onset of degradation temperature of each specific component. The crosslinking process was monitored by Raman spectroscopy for 12 hours consecutive, obtained by heating in Raman spectrometer at temperatures of 50, 100, 125 and 150°C and room temperature for nine days. The monitoring results indicate that cure of the paint primer showed better cure temperature to 100°C with the best curing time around 4 hours and the topcoat with curing temperature of 50°C with the best curing time around 8 hours.